(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the effect of Box Jump training on enhancing explosive power in the long jump among eighth-grade students at SMPN 3 Tolitoli. The Box Jump training method is a plyometric exercise designed to improve lower limb strength and explosiveness. This experimental study used a one-group pretest-posttest design with purposive sampling. Fourteen male students participated as subjects. The students were measured on their long jump performance before and after a six-week Box Jump training program. Data analysis using a t-test showed a significant increase in jump distance after the intervention, with t-count (2.278) > t-table (2.160) at a 5% significance level. Thus, Box Jump training significantly improved long jump explosive power.